Hemostatic abnormalities in children with thalassemia major and liver iron overload - Pustika Amalia Wahidiyat; Stephen Diah Iskandar; Novie Amelia Chozie; Damayanti Sekarsari (Paediatrica Indonesiana, 2018)
Background Thalassemia major (TM) patients are susceptible to liver dysfunction due to iron deposition. Pediatric TM patients often present with bleeding. Blood loss necessitates transfusions, leading to increased iron absorption from the gut. Objective To study hemostatic abnormalities in children with TM and iron deposition in the liver. Methods This cross-sectional study involved 190 non-splenectomized children with TM. Liver iron deposition was evaluated using T2* MRI. Prothrombin time (PT), activated partial thromboplastin time (aPTT), and platelet counts were assessed from blood specimens. Results Most subjects were diagnosed with β-thalassemia and β-thalassemia/HbE. The majority of subjects were on deferiprone (DFP) treatment. Approximately 89.5% of subjects had liver iron overload. Prolongation of PT and aPTT, as well as thrombocytopenia were observed in 60%, 27.9%, and 19.5% of subjects, respectively. Prolonged aPTT and thrombocytopenia were observed three times more frequently in subjects with moderate - severe liver iron overload than in subjects with normal - mild liver iron overload (P=0.04 and 0.001, respectively). Conclusion Most TM subjects have liver iron overload ranging from mild to severe. Prothrombin time and prolongation, as well as aPTT prolongation, and thrombocytopenia are easily found in TM children. There were significantly more moderate - severe liver iron deposition patients with aPTT prolongation and thrombocytopenia than normal – mild patients with these conditions. Hence, we suggest that pediatric TM patients undergo liver iron deposition evaluations and use iron chelators in an optimal manner, in order to limit the risk of bleeding.